Sports nutrition and doping factors in synchronized swimming: parallel analysis among athletes and coaches - Furjan-Mandic, G.; Peric, M.; Krzelj, L.; Stankovic, S.; Zenic, N. (Journal of Sports Science & Medicine, 2013)
Although nutrition and doping are important factors in sports, neither is often investigated in synchronized swimming (Synchro). This study aimed to define and compare Synchro athletes and their coaches on their knowledge of sports nutrition (KSN) and knowledge of doping (KD); and to study factors related to KSN and KD in each of these groups. Additionally, the KSN and KD questionnaires were evaluated for their reliability and validity. Altogether, 82 athletes (17.2 ± 1.92 years of age) and 28 coaches (30.8 ± 5.26 years of age) from Croatia and Serbia were included in the study, with a 99% response rate. The test and retest correlations were 0.94 and 0.90 for the KD and KSN, respectively. Subjects responded equally to 91% queries of the KD and 89% queries of the KSN. Although most of the coaches are highly educated, they declared self-education as the primary source of information about doping and sport-nutrition. Coaches scored higher than their athletes on both questionnaires which defined appropriate discriminative validity of the questionnaires. Variables such as age, sports experience and formal education are positively correlated to KSN and KD scores among athletes. The athletes who scored better on the KD are less prone to doping behavior in the future. These data reinforce the need for systematic educational programs on doping and sports nutrition in synchronized swimming. Special attention should be placed on younger athletes.